Evidence of an amnesia-like cued-recall memory impairment in nondementing idiopathic Parkinson's disease. (October 2015) - Edelstyn, Nicola M.J.; John, Christopher M.; Shepherd, Thomas A.; Drakeford, Justine L.; Clark-Carter, David; Ellis, Simon J.; Mayes, Andrew R.
Abstract: Medicated, non-dementing mild-to-moderate Parkinson's disease (PD) patients usually show recall/recollection impairments but have only occasionally shown familiarity impairments. We aimed to assess two explanations of this pattern of impairment. Recollection typically improves when effortful planning of encoding and retrieval processing is engaged. This depends on prefrontally-dependent executive processes, which are often disrupted in PD. Relative to an unguided encoding and retrieval of words condition (C1), giving suitable guidance at encoding alone (C2) or at encoding and retrieval (C3) should, if executive processes are disrupted, improve PD recollection more than control recollection and perhaps raise it to normal levels. Familiarity, being a relatively automatic kind of memory, whether impaired or intact, should be unaffected by guidance. According to the second explanation, PD deficits are amnesia-like and caused by medial temporal lobe dysfunction and although poorer recollection, which is caused by hippocampal disruption, may be improved by guidance, it should not improve more than control recollection. Familiarity impairment will also occur if the perirhinal cortex is disrupted, but will be unimproved by guidance. Without guidance, recollection/recall was impaired in thirty PD patients relative to twenty-two healthy controls and remained relatively equally impaired when full guidance was provided (C1 vs C3), both groups improving to broadly the same extent. Although impaired, and markedly less so than recollection, familiarity was not improved by guidance in both groups. The patients showed elevated rates of subclinical depressive symptoms, which weakly correlated with recall/recollection in all three conditions. PD executive function was also deficient and correlated with unguided/C1 recollection only. Our results are consistent with a major cause of the patients' recall/recollection impairments being hippocampal disruption, probably exacerbated by subclinical depressive symptoms. However, the results do not exclude a lesser prefrontal cortex contribution because patient executive functions were impaired and correlated solely with unguided overall recollection.